Computed tomography analysis of multicorer IP21_005MUC, core 1 - Jürgen Titschack; Sophia Stavrakoudis; Massimiliano Molari; Batuhan Çağrı Yapan; Felix Janssen; Christian Timann; Arne-Jörn Lemke (PANGAEA, 2024)
Selected multicorer cores and ROV push cores (IP21_021-17, IP21_021-18, IP21_061, IP21_061-19, IP21_061-20) of R/V Island Pride cruise IP21 were scanned using a Philips Brilliance iCT Elite 256 computer tomograph (CT) at the hospital Klinikum Bremen-Mitte, with an X- ray source voltage of 120 kV and a current of 300 mA. The CT image stacks have a physical resolution of 0.293 mm in the x and y directions and 0.625 mm resolution in the z direction (collimation; 0.3 mm reconstruction interval). Images were reconstructed using the filtered Back Projection (fBP) mode and a bone kernel (YB (Enhanced)). The data were processed with the ZIB edition of the Amira software (version 2019.51; Stalling et al., 2005; http://amira.zib.de). Within Amira, the core liners, including about 2 mm of the core rims, were deleted from the data set. Mangan nodules with diameters >~1 mm, open bioturbation traces, an unidentified organism, the natural bioturbated and surficial homogenised sediment were segmented by a marker-based watershed segmentation and visualized in 3D. Subsequently, the sediment components were quantified (MaterialStatistics module; volume per slice) and the mean and standard deviation of the sediment x-ray attenuation (MaterialStatistics module; statistics per slice per label; to avoid marginal averaging effects the sediment label was reduced by three voxels) were determined.